Proposed policy solutions for improving the disaster early warning system in Vietnam to increase the efficiency of loss mitigation, prevention - Thanh Nga, Pham Thi; Trinh, Ta Doan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The devastation of natural disaster is not only related to the danger level of phenomena but also depends on the prevention/mitigation capacity of the community. Early warning is the early recognition on disasters, an essential component of risk reduction, an important tool to protect lives and minimize material losses that may be caused by disasters. Effective operation of an early disaster warning system requires all of four interconnected components in the system, and controlled by mechanism, policies and legislation related to different management agencies from central to local level. This paper will make in-depth analysis on the position of the disaster early warning system in the legal document system relating to disaster management issued from early 1990s until the Law on Disaster Prevention officially took effect in May, 2014. The four main components of the disaster early warning systems was reviewed to see clearly the gap between policy and implementation with a view to making recommendations for improvement of the disaster early warning system and increased efficiency of the disaster risk management in Vietnam. Code: 15051401